2021
DOI: 10.3390/atmos12010075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Small-Scale Wildfires on the Air Parameters near the Burning Centers

Abstract: The results of seminatural experiments on the study of steppe and field wildfires characteristic of the steppe and forest-steppe zones of Western Siberia are presented. Using infrared (IR) thermography methods, the main thermal characteristics of the fire front are derived, the flame turbulence scale is estimated, and changes in the structure function of the air refractive index are analyzed in the vicinity of a fire. The effect of a model fire on the change of meteorological parameters (wind velocity componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…It should be noted that intense heat release in the combustion zone, and dissipation of large-scale turbulent structures in the flame lead to the formation of induced atmospheric turbulence even in mesoscale studies of wildfires, which was pointed in the work 12 . One should take into account this fact in order to develop models of wildfires effect on global climatic processes.…”
Section: Discussionmentioning
confidence: 95%
“…It should be noted that intense heat release in the combustion zone, and dissipation of large-scale turbulent structures in the flame lead to the formation of induced atmospheric turbulence even in mesoscale studies of wildfires, which was pointed in the work 12 . One should take into account this fact in order to develop models of wildfires effect on global climatic processes.…”
Section: Discussionmentioning
confidence: 95%
“…The extracted vehicular sensor data have various potential uses, for example, meteorological stats such as temperature and barometric pressure could be used to improve the current RWM based on stationary RWS by taking advantage of the inherent mobility of vehicles, enabling the identification of areas where ice is more probable to be formed due to low-temperature values, as well as inferring forest fire likelihood, as atmospheric pressure is proportional to ambient temperature and inversely proportional to humidity. It can also be used in extreme cases to detect forest fires, as barometric pressure suddenly drops in the vicinity of forest fires due to the pressure deficit created by oxygen consumption [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Convective transport in the flame, the release of significant amounts of heat in the combustion site, and the evolution of turbulent structures are certainly significant factors that affect the atmosphere as a result of the combustion site. The model fire in [11] increases the vertical component of wind speed near the combustion source, changes the relative humidity, and changes the temperature as a result of the fire. It has been found that the structural index of the fluctuation of sound speed and the fluctuation of the refractive index of the atmosphere, calculated by optical and acoustic methods, increases by an order of magnitude.…”
Section: Characterization Of Experimental Conditions and Analysis Of ...mentioning
confidence: 99%
“…The thermal energy released by wildland fires is transformed into turbulent processes in the flame, which create turbulence above the combustion source [11], which influences wind speed, air temperature, and humidity, as well as induced atmospheric turbulence. Studies of the transfer of gaseous and condensed combustion products during wildland fires are presented in [2,[12][13].…”
Section: Introductionmentioning
confidence: 99%